PERANCANGAN PENERIMAAN PESERTA DIDIK BARU BERBASIS WEBSITE MENGGUNAKAN METODE AGILE (STUDI KASUS : SMK KARTIKA XIX-3 KOTA CIREBON) - Sari, Tri Mulia; Muhammad Hatta; Chairun Nas (Universitas Methodist Indonesia, 2024)
This study aims to design a website-based new student admissions information system using the Agile method at SMK Kartika XIX-3 Cirebon City. The current information system still uses a manual method that requires significant time and effort and has the potential to cause errors in the administration process. Therefore, a more efficient system is needed to improve the effectiveness and efficiency of the new student admissions process. The Agile method was chosen because of its iterative and flexible approach, allowing adaptation to changing needs during the development process. The design process involves several stages, namely planning, gathering needs, system design, implementation, and testing. This information system is designed to facilitate the registration of new students, provide features for prospective student data management, and facilitate communication between schools and prospective students. The results of this study are a website-based information system that can be accessed online, facilitating the registration process and management of new student data. The system trial showed that this application meets user needs with a user-friendly interface and features that are in accordance with the initial specifications. With this system, it is expected that the process of accepting new students at SMK Kartika XIX-3 Cirebon City will be more effective, efficient, and transparent.